2022
DOI: 10.15212/zoonoses-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Global Control of Tuberculosis: Current Status and Future Prospects

Abstract: Tuberculosis is a zoonotic disease that is caused by mycobacterium tuberculosis complex and can infect humans, livestock, and wildlife. It spreads primarily through the respiratory tract and was the leading cause of death due to a single infectious disease before the COVID-19 pandemic. TB is a global public health emergency that has reemerged over the past few decades. Substantial efforts are needed to achieve the goals of the End TB Strategy. The World Health Organization has estimated that approximately 9.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…According to the World Health Organization (WHO) 2021 Global Tuberculosis Report, there were 10 million new TB cases and 1.3 million deaths worldwide in 2020 ( 1 ). Previous studies have shown that about one-third of the world’s population has been infected with TB, but only 10% develop active TB, meaning that nearly 90% of people experience latent tuberculosis infection (LTBI) ( 2 , 3 ). LTBI is a particular state in which an individual is infected with Mycobacterium tuberculosis that has not yet developed to active TB (ATB), characterized by a positive tuberculin skin test (TST) without clinical manifestations and imaging changes of ATB.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO) 2021 Global Tuberculosis Report, there were 10 million new TB cases and 1.3 million deaths worldwide in 2020 ( 1 ). Previous studies have shown that about one-third of the world’s population has been infected with TB, but only 10% develop active TB, meaning that nearly 90% of people experience latent tuberculosis infection (LTBI) ( 2 , 3 ). LTBI is a particular state in which an individual is infected with Mycobacterium tuberculosis that has not yet developed to active TB (ATB), characterized by a positive tuberculin skin test (TST) without clinical manifestations and imaging changes of ATB.…”
Section: Introductionmentioning
confidence: 99%
“…It is also the second leading cause of death (only behind COVID-19) among infectious diseases, with mortality nearly double that of human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) [ 2 ], with the first year-over-year increase in 2020 despite years of effort to end TB. The difficulty associated with TB diagnosis is believed to be one of the major obstacles to successful prevention and control of the disease [ 3 ]. In 2020, 41.4% to 47.3% of cases failed to be diagnosed and reported [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence and mortality of lung cancer have decreased significantly in the past decade, it is still one of the leading causes of death, which greatly impairs people’s life and health ( 1 ). Every year, there is about 2.2 million new cases and 1.79 million deaths according to conservative estimation ( 2 , 3 ). Lung cancer can be divided into two main types, non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC), among which NSCLC is the major one ( 4 ).…”
Section: Introductionmentioning
confidence: 99%